INVESTIGATING EARLY-CAREER TEACHERS’ ADAPTATION CHALLENGES: A CASE OF INDONESIAN EFL TEACHERS - Yogi Saputra Mahmud (PROJECT (Professional Journal of English Education), 2020)
Teacher professional development has recently become a central focus in the Indonesian context, particularly after the implementation of the post-bachelor teacher professional education program or Pendidikan Profesi Guru (PPG) for both pre-service and in-service EFL teachers in 2013. However, studies reveal that the transition from teacher education programs to the initial teaching career at schools has been described as a challenging phase. Despite the growing attention of scholars in exploring beginning teachers’ challenges, studies focusing on the early-career Indonesian EFL teachers, particularly those who just completed the PPG program, are considered limited. Therefore, drawing on a qualitative case study with two beginning Indonesian secondary EFL teachers, this study aims to unravel the challenges during their first-year teaching experience at school after completing the PPG program. By thematically analysing the semi-structured interviews, this study indicated that the teachers experienced four significant challenges: 1) pedagogical (classroom management, lack of teaching resources, test-based learning atmosphere), 2) professional (complex self-identification), 3) social (maintaining rapport with senior teachers), and 4) personal (mood management).  Despite having been trained professionally through the PPG program, the result suggested that the beginning teachers still faced considerable challenges during their initial endeavour as an English teacher at school. Pedagogical implications are discussed in terms of the need for continuous professional development for the newly certified teachers during their initial career at schools.